2013
DOI: 10.1111/1750-3841.12205
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Hepatitis A Virus on FRhK‐4 Cells Treated with Korean Red Ginseng Extract and Ginsenosides

Abstract: Red ginseng has a variety of bioactive functions and is widely used as an oriental medicinal herb and food ingredient. The aim of this study was to investigate the antiviral effect of red ginseng extract and ginsenosides against hepatitis A virus (HAV). To examine the antiviral effect against HAV, 0 to 10 μg/mL of red ginseng and purified ginsenoside Rb1 and Rg1 were pre-treated or co-treated on FRhK-4 cells. The HAV titer decreased significantly in all groups pretreated with red ginseng or purified ginsenosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…These findings are in agreement with the study conducted with PE (persimmon extract) where no significant effect pre-or postinfection was reported and that the maximal antiviral activity was obtained by direct treatment of the virus particles (Ueda et al 2013). Similar findings were reported for ginsenoside extract (5 lg/mL) treatment against HAV, where a very low reduction in titer was reported when the host cells were pretreated with the extract (Lee et al 2013). Similar results with GSE on viral adsorption of FCV-F9, MNV-1, and HAV were previously reported, with less effect on replication (Su and D'Souza 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in agreement with the study conducted with PE (persimmon extract) where no significant effect pre-or postinfection was reported and that the maximal antiviral activity was obtained by direct treatment of the virus particles (Ueda et al 2013). Similar findings were reported for ginsenoside extract (5 lg/mL) treatment against HAV, where a very low reduction in titer was reported when the host cells were pretreated with the extract (Lee et al 2013). Similar results with GSE on viral adsorption of FCV-F9, MNV-1, and HAV were previously reported, with less effect on replication (Su and D'Souza 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study, GSE at 1 mg/ml was shown to reduce HAV titers from initial 5 log PFU/ml by 2.89 log PFU/ml after 2 h at 37°C (Su and D'Souza 2011). HAV titers at initial 5.74 log PFU/ml were also shown to be decreased by 0.66 log PFU/ml when treated with 10 lg/mL Korean red ginseng, and decreased by 0.37 log PFU/ml when treated with 10 lg/mL purified ginsenoside extract after 24 h at 37°C (Lee et al 2013). BB-PAC treatment, although at a higher concentration, was found to be effective in reducing HAV titers where 2 mg/ ml BB-PAC caused reduction to undetectable levels within 30 min at 37°C.…”
Section: Discussionmentioning
confidence: 87%
“…Liver cirrhosis is a state requiring close monitoring, as it is the state preceding liver carcinoma. RG and its constituents, ginsenosides Rg1 and Rb1, have been shown to exhibit a hepatoprotective effect against hepatitis virus A by decreasing hepatitis virus titers [38]. Drugs for chronic hepatitis virus C have been developed but pose a practical problem owing to their cost, as the full drug regimen for hepatitis virus C is extremely expensive.…”
Section: Multiple Efficacies For Hepatic Injuriesmentioning
confidence: 99%
“…Red ginseng (P. ginseng) and ginsenosides Rg1 and Rb1 could decrease hepatitis A virus (HAV) titers (Lee et al, 2013b). Ginseng extract is active against respiratory syncytial virus infection (Lee et al, 2014c).…”
Section: Antimicrobial Activitymentioning
confidence: 99%